Estrutura da comunidade de invertebrados aquáticos em arrozais do Rio Grande do Sul - Stenert, Cristina (Universidade Federal de São Carlos, 2009)
Wetlands are prioritary ecosystems for conservation due to their vast biological diversity and productivity, besides their many functions and value. In southern Brazil conservative data show that about 90% of the original wetlands are already destroyed due to agricultural expansion, mainly the irrigated rice fields. On the other hand, rice is the most important cereal grown in developing countries, being the main food source for more than half of the world population. Also, a high diversity of plants and animals has been found in these agricultural areas. The main goal of this study was to assess the structure and diversity of macroinvertebrates in rice fields and irrigation canals over the different hydrological phases of the cultivation cycle in an important rice cultivation area in Rio Grande do Sul to preserve the biota in these agroecosystems. Six collections were carried out along a cultivation cycle (June 2005 June 2006) in six rice fields and four irrigation canals in the Coastal Plain of Rio Grande do Sul. Quantitative samples of macroinvertebrates were obtained with a corer inserted 10 cm deep into the sediment, and also qualitative samples with a kick net.The main results obtained were: a total of 26,579 individuals assigned into 119 invertebrate taxa were collected in rice fields and irrigation canals; the maintenance of the dry fields and the flooded fields in the fallow phase favors the setting of a greater amount of macroinvertebrate taxa in the agricultural landscape; the irrigated rice fields can store and keep egg banks and other resistance structures of aquatic invertebrates viable along their cultivation cycle, and the irrigation canals work as habitats for the aquatic invertebrate community, thus assisting to keep the aquatic diversity in these agricultural areas. These results can be used in management plans which aim at reconciling agricultural production and biodiversity conservation in Rio Grande do Sul.
Keywords: Macroinvertebrados bentônicos; Arroz - plantio; Diversidade biológica; Manejo de ecossistemas; Conservação da natureza; Dormência; Conservação de áreas úmidas; Manejo de agroecossistemas; Biodiversity; Benthic macroinvertebrates; Rice cultivating; Agroecosystem management; Wetland conservation; CIENCIAS BIOLOGICAS::ECOLOGIA